Divergent Gold‐Catalyzed Rearrangement of 1‐Alkenyl‐2‐alkynylcyclopropanes: Enyne Transformation Controlled by a Silicon Moiety. Issue 18 (7th August 2020) - González, Jairo; Allegue, Darío; Fernández, Sergio; Rodríguez, Miguel A.; Santamaría, Javier; Ballesteros, Alfredo
Abstract: Here we report a gold(I)‐catalyzed rearrangement for a special type of alkynylcyclopropanes, such as (6‐ethynylbicyclo[3.1.0]hex‐2‐en‐6‐yl)silanes. These enynes evolved through an isomerization reaction towards the formation of isomeric alkynylcyclopropanes instead of the expected alkynylcyclohexadienes. A computational study on the reaction mechanism revealed the participation of a polycyclic gold(I) carbene complex as intermediate instead of a σ‐allylic gold cation which is in agreement with the expected influence in the energy of those intermediates due to the presence of the silyl group. Finally, this gold(I) carbene intermediate could be experimentally intercepted through intramolecular cyclopropanations. Abstract :